Targeting protein for Xenopus kinesin-like protein 2 (TPX2) regulates γ-Histone 2AX (γ-H2AX) levels upon ionizing radiation - Neumayer, Gernot; Gruss, Oliver (The journal of biological chemistry, 2012)
The microtubule-associated protein targeting protein for Xenopus kinesin-like protein 2 (TPX2) plays a key role in spindle assembly and is required for mitosis in human cells. In interphase, TPX2 is actively imported into the nucleus to prevent its premature activity in microtubule organization. To date, no function has been assigned to nuclear TPX2. We now report that TPX2 plays a role in the cellular response to DNA double strand breaks induced by ionizing radiation. Loss of TPX2 leads to inordinately strong and transient accumulation of ionizing radiation-dependent Ser-139-phosphorylated Histone 2AX (γ-H2AX) at G0 and G1 phases of the cell cycle. This is accompanied by the formation of increased numbers of high intensity γ-H2AX ionizing radiation-induced foci. Conversely, cells overexpressing TPX2 have reduced levels of γ-H2AX after ionizing radiation. Consistent with a role for TPX2 in the DNA damage response, we found that the protein accumulates at DNA double strand breaks and associates with the mediator of DNA damage checkpoint 1 (MDC1) and the ataxia telangiectasia mutated (ATM) kinase, both key regulators of γ-H2AX amplification. Pharmacologic inhibition or depletion of ATM or MDC1, but not of DNA-dependent protein kinase (DNA-PK), antagonizes the γ-H2AX phenotype caused by TPX2 depletion. Importantly, the regulation of γ-H2AX signals by TPX2 is not associated with apoptosis or the mitotic functions of TPX2. In sum, our study identifies a novel and the first nuclear function for TPX2 in the cellular responses to DNA damage.